Comparative review: clinical and pathological heterogeneity in knee versus temporomandibular joint osteoarthritis - Zhao, Jiannan; Wang, Ruoyi; Zhu, Songsong; Li, Zhen; Ren, Rong; Jiang, Nan (Frontiers in Bioengineering and Biotechnology, 2025)
Temporomandibular joint osteoarthritis (TMJOA) remains a clinically underrecognized and insufficiently studied disorder, despite exerting a comparable impact on quality of life as knee osteoarthritis (knee OA). TMJOA can lead to chronic pain, limited mouth opening, joint dysfunction, and craniofacial deformities, yet it receives disproportionately less research attention and lacks standardized diagnostic and therapeutic frameworks. While TMJOA and knee OA share several hallmark pathological features—including cartilage degeneration, subchondral bone remodeling, and synovitis—these manifestations are shaped by joint-specific anatomical and biomechanical environments, resulting in distinct disease trajectories. Current evidence highlights that the pathogenesis of TMJOA remains poorly defined, with unresolved questions surrounding the role of mechanical loading in altering the cartilage microenvironment, the mechanisms underlying pathological calcification, and the influence of sex hormones such as estrogen and progesterone on disease onset and progression. In contrast, decades of knee OA research have yielded validated preclinical models, detailed molecular insights, and emerging regenerative strategies. This review systematically compares the two forms of osteoarthritis from clinical, anatomical, and pathological perspectives. We propose that TMJOA research may benefit significantly from cross-joint insights derived from the more extensively studied knee OA. Cross-comparative approaches not only provide a valuable framework for understanding joint-specific disease mechanisms but also offer new directions for the development of targeted therapies and diagnostic tools tailored to TMJOA. Bridging the current knowledge gap through interdisciplinary and translational research may ultimately improve outcomes for patients affected by this overlooked joint disease.